Impact of Capping Agent Incorporation on pH Stability of Silver Diamine Fluoride: An in Vitro Analysis - Mehmood Asghar; Ros Anita Omar; Adrian UJin Yap; Nida Zehra Bano; Rosiyah Yahya; Ahmad Danial Azzahari (Life and Science)
Objective: To determine the chemical stability by evaluating time-dependent pH changes in 38% silver diamine fluoride with or without incorporating different concentrations of tannic acid and glutathione as capping agents. Study Design: Experimental, in vitro study. Place and Duration of Study: The study was conducted at the Faculty of Dentistry, University of Malaya, Kuala Lumpur, Malaysia from January 2021 to April 2022. Methods: Tannic acid and Glutathione-modified silver diamine fluoride solutions were prepared by incorporating tannic acid or Glutathione at different concentrations (5,10,15% w/v) into silver diamine fluoride. pH changes in the solutions were measured at different time points: from 1 hour after the bottles were opened to day 90. Results: The pH of 38% silver diamine fluoride from baseline till day-90 ranged between 7.73±0.02 and 7.69±0.01. The incorporation of tannic acid and glutathione resulted in a significant increase in the pH of the silver diamine fluoride solution. In tannic acid-modified silver diamine fluoride, the highest 90-day pH was shown by silver diamine fluoride + 5% tannic acid (w/v) (9.00±0.01), while in the glutathione-modified silver diamine fluoride, silver diamine fluoride + 15% Glutathione (w/v) had the highest 90-day pH (9.80±0.02). Repeated measures analysis of variance showed a statistically significant difference between the groups' pH values. A pairwise comparison showed significant differences in the pH of all the possible pairs at all-time points (P<0.05), except the pairs silver diamine fluoride + 15% tannic acid (w/v) and silver diamine fluoride + 15% glutathione (w/v) after the 1st hour and day 1 (P > 0.05). Conclusion: Silver diamine fluoride and tannic acid/glutathione-modified silver diamine fluoride solutions remain stable for up to 90 days. Capping agent incorporation significantly increases the pH of silver diamine fluoride, thereby enhancing its long-term stability and shelf life.